Women Aesthetics in Pundi Bank Advertisement from Cultural Studies Perspective - Anak Agung Gde Bagus Udayana (Mudra: Jurnal Seni Budaya, 2018)
Women aesthetics that are visualized in the billboard advertisement of Pundi Bank is a strategic activity to persuade consumer or society. This is intended to see the picture of female aesthetics and its significance in contemporary society through the billboard advertisement of Pundi Bank by identifying the signs contained. The method that is used in this study is semiotics. Semiotics is essentially a qualitative interpretative (interpretation) method that focuses on sign and text as a study object as well as on how researchers interpret and understand the code (decoding) of the sign and the text. This study gives the aesthetic female image presented in the ad message it appears to be of the election of the visual communication element, It’s like photographic illustration, text, and color. The elements are arranged in such a harmony with the use of asymmetrical balance, making it look more attractive with a protrusion on the photographic illustration. The meaning that is delivered by Pundi Bank from this advertisement is a reflection of women’s lifestyle reality in contemporary society. Furthermore, this advertisement is formed by many icons in which it can be interpreted as a symbol of contemporary woman. Besides that, Pundi Bank advertisement also has a construction of social reality which can be seen as denotative and connotative meaning.